Hukum Transeksual Perspektif Hukum Islam Berbasis Paradigma Maqosid Al Syari’ah - Yani, Ahmad; Mukhlas, Oyo Sunaryo (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The beauty of the human body shape still has various phenomena since he was born, there are those who are physically perfect and genetically perfect. On the other hand, there are also humans who are born with imperfect physical and genetic forms. In today's modern era, the existence of genital surgery has positive implications for people who are born with abnormal genitalia, such as men or women who have imperfect or double sex or are performed by men or women with genital organs. perfect sex but has a physical form similar to that of a man or a woman and it is this type that is often misused to perform genital change operations from male to female and female to male. Referring to the factors that have been stated above, the phenomenon of reassignment surgery or sex change is caused by physical factors and the sex itself. Therefore, the focus of the discussion in this article is on the implementation of transsexuals in the legality of reassignment surgery or sex change in Shari'ah in terms of the perspective of Islamic law based on the maqashid al-shari'ah paradigm. Keywords: Transsexual, Islamic Law, Maqashid al-Syariah